Effects of pharmacological block of GABAA receptors on pallidal neurons in normal and parkinsonian state - Xue, Yan; Han, Xiao-Hua; Chen, Lei (Frontiers in Cellular Neuroscience, 2010)
The globus pallidus plays a central integrative role in the basal ganglia circuitry. Morphological studies have revealed a high level of GABA and GABAA receptors in the globus pallidus. To further investigate the effects of endogenous GABAA neurotransmission in the globus pallidus of normal and parkinsonian rats, in vivo extracellular recording and behavioral tests were performed in the present studies. In normal rats, micro-pressure ejection of GABAA receptor antagonist gabazine (0.1 mM) increased the spontaneous firing rate of pallidal neurons by 28.3%. Furthermore, in 6-hydroxydopamine parkinsonian rats, gabazine increased the firing rate by 46.0% on the lesioned side, which was significantly greater than that on the unlesioned side (21.5%, P<0.05), as well as that in normal rats (P<0.05). In the behaving rats, unilateral microinjection of gabazine (0.1 mM) evoked consistent contralateral rotation in normal rats, and significantly potentiated the number of apomorphine-induced contralateral rotations in parkinsonian rats. The present electrophysiological and behavioral findings may provide a rational for further investigations into the potential of pallidal endogenous GABAA neurotransmission in the treatment of Parkinson’s disease.